KEMAMPUAN MULTIREPRESENTASI VERBAL DAN TABEL MAHASISWA PENDIDIKAN FISIKA SEMESTER 5 PADA MATERI KARAKTERISTIK GELOMBANG ELEKTROMAGNETIK - Hasanah, Uswatun; Sudarti, Sudarti (Eduscience : Jurnal Ilmu Pendidikan, 2021)
The purpose of writing this article is to determine the effectiveness of verbal and table multi- representation learning for 5th semester physics students on the characteristics of electromagnetic waves. The background of this article is that there are many physics students who have low verbal and table multirepresentation abilities, so this research needs to be done in order to find out the multi-presentation ability of physics students which can be seen from the results of their answers when solving problems on the characteristics of electromagnetic waves. The data collection process is carried out with a survey method of knowledge tests using a questionnaire on the google form application. The method used is a quantitative method, namely by collecting data, then analyzing it. The population of this study were 50 physics education students while the sample was fifth semester students who were studying the characteristics of electromagnetic waves. With the data collection method above, the results obtained are the results of the multi-representation in the form of a table which is higher than the multi-representation in the form of a verbal. Therefore, this multi-representation learning strategy in the form of a table can be a solution to increase student knowledge on the material characteristics of electromagnetic waves.Key words: multipresentation, learning, electromagnetic waves